Fibrin-associated diffuse B-cell lymphoma after endovascular aneurysm repair can mimic a mycotic aneurysm - Joshua T. Geiger, MD, MS; Alaska Pendleton, MD, MPH (Journal of Vascular Surgery Cases and Innovative Techniques)
Fibrin-associated diffuse large B-cell lymphoma is a rare malignancy that can arise after vascular surgical procedures. Importantly, it can mimic culture-negative aortic graft infection with elevated inflammatory markers and avidity on positron emission tomography. Chemotherapy is the mainstay of treatment. This case highlights the challenges in the diagnosis and perioperative management of a patient with such a disease after complex endovascular aortic surgery.